Dietary Fruit By-Products Improve the Physiological Status of Nile Tilapias (Oreochromis niloticus) and the Quality of Their Meat - Chotolli, Andrey P. [UNESP]; da Fonseca, Victor E. [UNESP]; Bermejo-Poza, Rubén; Ferraz, Isabella G. [UNESP]; de Souza, Letícia C. C. [UNESP]; Brasil, Mariana L. [UNESP]; Santana, Ronnie F. [UNESP]; Games, Isadora M. M. [UNESP]; Ferraz, Murilo C. [UNESP]; Theophilo, Gabrielly [UNESP]; Salmaso, Pedro H. L. [UNESP]; Balbino, André L. S. [UNESP]; et al. (MDPI, 2023)
By-products from fruit industrialization retain nutritional and functional components; thus, they may find use in animal feeding. This study aimed to assess the effects of dietary fruit industrial by-products on the tilapias blood biochemical and oxidative parameters and on the composition and lipid peroxidation of their fillets. Four diets were supplied to the tilapias: a C-control diet, with no fruit meal, and three diets containing 5% of either acerola (ACM), apple (APM) or grape (GRM) meal. The phenolic compounds and the carotenoids in the meals and their antioxidant capacities were measured. Fish were weighed and measured for the calculation of the growth performance data, their blood was analyzed for health and oxidative status biomarkers and their fillets were analyzed for proximal composition and lipid peroxidation. Grape meal had the highest concentration of phenolics and carotenoids and the highest antioxidant activity, followed by acerola and apple meals. The productive performance was similar among the treatments. The fruit by-product diets either maintained or improved the biochemical biomarkers of health and improved the oxidative status of the fish. The fruit by-product diets increased the concentration of lipids in the fillets and slowed down the onset of the lipid peroxidation during frozen storage.
Keywords: acerola; apple; carotenoids; grape; lipid peroxidation; phenolic compounds